Changes in Japanese eyes after laser peripheral iridotomy: an anterior segment optical coherence tomography study. (5th February 2016) - Ang, Bryan CH; Nongpiur, Monisha E; Aung, Tin; Mizoguchi, Takanori; Ozaki, Mineo
Abstract: Background: The aim was to investigate the changes in anterior segment parameters, as assessed by anterior segment optical coherence tomography in Japanese subjects after laser peripheral iridotomy (LPI). Design: This was a prospective observational study. Participants: The participants include 72 subjects with angle closure including primary angle closure suspect (PACS), primary angle closure (PAC), and primary angle closure glaucoma (PACG). Methods: Anterior segment optical coherence tomography parameters was measured by customized software. Complete data of 51 subjects were available for final analysis. Main Outcome Measures: These were the following parameters: angle opening distance, trabecular‐iris space area, anterior chamber depth, width, area and volume (iris thickness, curvature, and area, and lens vault (LV). Results: A total of 25 PACS, 17 PAC and 9 PACG were included. Mean age was 74.7 ± 6.7 years, and majority were women (80.4%). Following LPI, there was a significant increase in mean gonioscopic angle width (1.16 vs. 1.93, P  < 0.001) and a corresponding increase in angle opening distance, trabecular‐iris space area, and angle recess area (all P  < 0.001). The anterior chamber area ( P  < 0.001), anterior chamber volume ( P  < 0.001) and anterior chamber depth ( P  = 0.003) increased significantly; and iris curvature ( P  < 0.001) was significantly reduced. There were no significant changes in anterior chamber width, LV, iris thickness and area. Age‐adjusted and gender‐adjusted analysis for predictors of percentage change in angle opening distance 750 showed significant association with greater baseline LV ( β  = 0.32, P  = 0.03). No significant differences were noted in the mean percentage change in parameters between the PACS and PAC‐PACG. Conclusions: An increase in anterior chamber dimensions, angle widening and iris flattening; with a constant LV, iris thickness and iris area after LPI was demonstrated in Japanese eyes with angle closure.